Cover Image, Volume 53, Number 10, September 2018. Issue 10 (21st September 2018) - Steuer, Guy; Prais, Dario; Mussaffi, Huda; Mei‐Zahav, Meir; Bar‐On, Ophir; Levine, Hagit; Gendler, Yulia; Blau, Hannah; Stafler, Patrick
Abstract : The cover image, by Guy Steuer MD et al., is based on the Original Article: Asthma Inspiromatic‐ safety and efficacy study of a new generation dry powder inhaler in asthmatic children, DOI:10.1002/ppul.24077